BUSINESS PLAN AS A MANAGING INSTRUMENT OF AGRIBUSINESS DEVELOPMENT - Ilić, Vukašin (Economics of Agriculture, 2008)
In this work are pointed out the reasons for reaffirmations of planning as instrument of management in developing of agribusiness. Especially are apostrophized foreseeing, planning and methodology of planning as professional questions. The answers of these questions are present in use of scientific knowledge modern management skills.